Quantum dot light-emitting device and preparation method thereof
The synthesis of CsPbBr3 perovskite quantum dot material through a single halogen Br and adding bitodental ligands is solved, and the problem of poor performance of perovskite quantum dot luminescent devices in the blue light band is achieved, achieving efficient and stable blue light emission and extended device life.
Patent Information
- Application Number
- CN202411883140.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing perovskite quantum dot light emitting devices have poor performance in the blue light band, and there are problems such as low color purity, low external efficiency and short device life. In addition, mixed halogen perovskite nanocrystalline materials will undergo halogen element phase separation under the action of electric field, affecting the wavelength stability of the light emitting diode.
The CsPbBr3 metal halide perovskite quantum dot material is synthesized by a single halogen Br, and the band gap of the material is increased by using the quantum confined domain effect, and 3,3'-[1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl]bis(propane-1-ammonium) bromide is added to the first precursor as a bidentate ligand, which is bound to the perovskite quantum dot surface to enhance surface stability and quantum confined domain effect.
It improves the spectral stability and luminous efficiency of perovskite quantum dot luminescence devices, extends the service life of the device, and achieves efficient luminescence in the blue light band.
Smart Images

Figure CN119604123A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of quantum dot luminescence technology, and in particular to a quantum dot luminescent device and a preparation method thereof. Background Art
[0002] Light-emitting diodes (LEDs) have surpassed traditional lighting sources and are profoundly changing the lighting and display industries. Today, a variety of materials are available for commercialized LEDs, such as III-V semiconductor LEDs, organic LEDs (OLEDs), and quantum dot LEDs (QLEDs). Blue, as one of the three primary colors, is an important component in lighting. OLEDs have become an alternative in the field of LEDs due to their solution and vacuum deposition capabilities, large-area light emission, and flexibility. However, low thermal and chemical stability under high brightness and high current density conditions severely limit the application of OLEDs. QLEDs exhibit excellent high color rendering index (CRI), high stability, and high efficiency, while core-shell quantum dots are difficult to achieve macroscopic manufacturing due to cumbersome manufacturing processes and expensive raw materials. All of these shortcomings hinder the progress of cost-effective multi-scenario electroluminescent applications. Finding promising electroluminescent materials is very important to promote the development of the lighting and display industries.
[0003] Metal halide perovskites (MHPs) are a promising new type of semiconductor material with the characteristics of low cost, spectral tunability and high photoluminescence quantum yields (PLQYs), which have broadened optoelectronic application scenarios. At present, the highest external quantum efficiency (EQE) of green perovskite LEDs (PeLEDs) and red PeLEDs exceeds 28%, which is comparable to traditional OLEDs and QLEDs. However, LEDs emitting in the blue band at around 470nm still lag behind green and red PeLEDs. Low color purity, moderate external efficiency and poor device lifetime are serious obstacles to the commercialization of perovskite light-emitting diodes. Therefore, when promoting the commercial development of PeLEDs, issues such as full width at half maximum (FWHM), reducing efficiency roll-off and extending the service life of devices should be considered.
[0004] At present, the main method of obtaining blue light using perovskite quantum dots is to add a certain amount of Cl element to CsPbBr3 perovskite quantum dots to prepare mixed halogen perovskite. However, the mixed halogen perovskite nanocrystalline material will undergo halogen element (Br, Cl) phase separation under the action of an electric field, resulting in a change in the spectrum, which in turn affects the wavelength stability of the light-emitting diode. In addition, the doping of Cl elements may also introduce more halogen defects into the nanocrystals, which in turn leads to a decrease in the performance and stability of the light-emitting device.
[0005] Therefore, it is necessary to develop a quantum dot light-emitting device and a preparation method thereof to solve the above problems. Summary of the invention
[0006] The purpose of the present invention is to design a quantum dot light-emitting device and a preparation method thereof in order to solve the above problems.
[0007] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0008] A quantum dot light-emitting device comprises a substrate printed with an ITO anode, a PEDOT:PSS hole transport layer, a PVK hole transport layer, a perovskite quantum dot light-emitting layer, a TPBi electron transport layer, a LiF electron transport layer, and an Al cathode, which are sequentially connected from one side to the other.
[0009] A method for preparing a quantum dot light-emitting device, comprising:
[0010] S1. Place the substrate printed with ITO anode in a mixed solution of anhydrous ethanol and deionized water, and use an ultrasonic machine to ultrasonicate for 20 minutes, and then blow dry the liquid on its surface with nitrogen;
[0011] S2, placing the dried substrate printed with ITO anode into UV cleaning agent and cleaning with UV ozone for 15 minutes;
[0012] S3, spin-coat the PEDOT:PSS film on a clean substrate printed with ITO anode using a coater and heat it on a hot plate for 15 minutes;
[0013] S4, placing the product treated in step S3 into a glove box filled with nitrogen, spin-coating PVK, and heating it on a hot plate for 20 minutes;
[0014] S5, after being cooled by the treatment of S4, spin-coating a perovskite quantum dot light-emitting layer on the PVK film at a rotation speed of 4000 rpm, and heating at 60° C. for 5 minutes;
[0015] S6: Place the product treated in S5 into the evaporation equipment and evacuate the air. When the air pressure is less than 5×10 -4 TPBi, LiF and Al thin films were evaporated at pa with thicknesses of 80nm, 1nm and 100nm, respectively.
[0016] Furthermore, the synthesis and purification process of the perovskite quantum dot light-emitting layer material includes the following steps:
[0017] S51, prepare two three-necked flasks, No. 1 and No. 2, each of which has a capacity of 100 ml, and place a stirring bar in each of the three-necked flasks;
[0018] S52, PbBr2, ZnBr2 and 3,3'-[1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl]bis(propane-1-ammonium) bromide are placed in a No. 1 three-necked flask, and octadecene is added as a solvent;
[0019] S53, adding Cs2CO3 and oleic acid into a No. 2 three-necked flask, and adding octadecene as a solvent;
[0020] S54, heating the solutions in the No. 1 three-necked flask and the No. 2 three-necked flask to 120° C. and evacuating the solution, and maintaining this condition with stirring for one hour, then filling the two three-necked flasks with nitrogen and continuing to stir;
[0021] S55, lowering the temperature of the two flasks to 100°C and adding oleic acid and oleylamine into the stirred three-necked flask No. 1, and evacuating the solution again after the solids in the solution are completely dissolved, and switching back to the nitrogen environment after 1 minute;
[0022] S56, heating the No. 1 three-necked flask to 150° C., taking 1 ml of the Cs-OA solution from the No. 2 three-necked flask and quickly injecting it into the No. 1 three-necked flask, reacting for 5 seconds, and then cooling the No. 1 three-necked flask in an ice bath to obtain a crude perovskite quantum dot solution;
[0023] S57. Add 20 ml of ethyl acetate to the cooled crude perovskite quantum dot solution and centrifuge it. Finally, redisperse it in an n-octane solution for storage.
[0024] Preferably, in step S52, the concentration of PbBr2 is 13.7 mg / ml.
[0025] Preferably, in step S52, the concentration of ZnBr2 is 51.15 mg / ml.
[0026] Preferably, the chemical formula of 3,3'-[1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl]bis(propane-1-ammonium) bromide is C 20 H 22 Br2N4O4, chemical structure formula is:
[0027] .
[0028] Preferably, in step S52, the amount of 3,3'-[1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl]bis(propane-1-ammonium) bromide added is in the range of 5-20 mg.
[0029] The beneficial effects of the present invention are:
[0030] (1) Using a single halogen Br to synthesize CsPbBr3 metal halide perovskite quantum dot material, the quantum confinement effect is used to increase the band gap of the material, rather than introducing the Cl element to adjust the band gap of the perovskite material. This fundamentally avoids the inherent problem brought about by mixed halogen perovskite nanocrystal materials: halogen phase separation under an electric field. This improves the spectral stability of the material;
[0031] (2) By adding a certain amount of 3,3'-[1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl]bis(propane-1-ammonium) bromide (TOPB2) into the first precursor as a bidentate ligand to bind to the surface of the perovskite quantum dots, the quantum dots are provided with stronger surface stability, which enhances their quantum confinement effect and shifts the emission wavelength of the CsPbBr3 mineral quantum dots to the blue light band. In addition, the Br atoms in TOPB2 can provide a halogen-rich environment for the quantum dot material, further enhancing the quantum confinement effect of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the structure of the quantum dot light-emitting device in the present invention.
[0033] The markings in the figure are: 1. Substrate with ITO anode printed on it, 2. PEDOT:PSS hole transport layer, 3. PVK hole transport layer, 4. Perovskite quantum dot light-emitting layer, 5. TPBi electron transport layer, 6. LiF electron transport layer, 7. Al cathode. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.
[0035] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0037] In the description of the present invention, it should be understood that the terms "upper", "lower", "inside", "outside", "left", "right", etc. indicate directions or positional relationships based on the directions or positional relationships shown in the figures, or are directions or positional relationships in which the product of the invention is usually placed when in use, or are directions or positional relationships commonly understood by those skilled in the art. These directions or positional relationships are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as a limitation on the present invention.
[0038] Furthermore, the terms “first”, “second”, etc. are merely used for distinguishing descriptions and should not be understood as indicating or implying relative importance.
[0039] In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms such as "setting" and "connection" should be understood in a broad sense. For example, "connection" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0040] The specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings.
[0041] like Figure 1 As shown, the quantum dot light-emitting device includes a substrate printed with an ITO anode, a PEDOT:PSS hole transport layer, a PVK hole transport layer, a perovskite quantum dot light-emitting layer, a TPBi electron transport layer, a LiF electron transport layer, and an Al cathode, which are sequentially connected from one side to the other.
[0042] A method for preparing a quantum dot light-emitting device, comprising:
[0043] S1. Place the substrate printed with ITO anode into a mixed solution of anhydrous ethanol and deionized water, and use an ultrasonic machine to ultrasonicate for 20 minutes, and then blow dry the liquid on its surface with nitrogen;
[0044] S2, placing the dried substrate printed with ITO anode into UV cleaning agent and cleaning with UV ozone for 15 minutes;
[0045] S3, spin-coat a PEDOT:PSS film on a clean substrate printed with an ITO anode using a coater and heat it on a hot plate for 15 minutes;
[0046] S4, placing the product treated in step S2 into a glove box filled with nitrogen, spin-coating PVK, and heating it on a hot plate for 20 minutes;
[0047] S5, after being cooled by the treatment of S3, spin coating the perovskite quantum dot light-emitting layer on the PVK film at a rotation speed of 4000 rpm, and heating at 60° C. for 5 minutes;
[0048] S6: Place the product treated in S4 into the evaporation equipment and evacuate the air. When the air pressure is less than 5×10 -4 TPBi, LiF and Al thin films were evaporated at pa with thicknesses of 80nm, 1nm and 100nm, respectively.
[0049] In some embodiments, the synthesis and purification process of the perovskite quantum dot light-emitting layer material includes the following steps:
[0050] S51, prepare two three-necked flasks, No. 1 and No. 2, each of which has a capacity of 100 ml, and place a stirring bar in each of the three-necked flasks;
[0051] S52, PbBr2, ZnBr2 and 3,3'-[1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl]bis(propane-1-ammonium) bromide are placed in a No. 1 three-necked flask, and octadecene is added as a solvent;
[0052] S53, adding Cs2CO3 and oleic acid into a No. 2 three-necked flask, and adding octadecene as a solvent;
[0053] S54, heating the solutions in the No. 1 three-necked flask and the No. 2 three-necked flask to 120° C. and evacuating the solution, and maintaining this condition with stirring for one hour, then filling the two three-necked flasks with nitrogen and continuing to stir;
[0054] S55, lowering the temperature of the two flasks to 100°C and adding oleic acid and oleylamine into the stirred three-necked flask No. 1, and evacuating the solution again after the solids in the solution are completely dissolved, and switching back to the nitrogen environment after 1 minute;
[0055] S56, heating the No. 1 three-necked flask to 150° C., taking 1 ml of the Cs-OA solution from the No. 2 three-necked flask and quickly injecting it into the No. 1 three-necked flask, reacting for 5 seconds, and then cooling the No. 1 three-necked flask in an ice bath to obtain a crude perovskite quantum dot solution;
[0056] S57. Add 20 ml of ethyl acetate to the cooled crude perovskite quantum dot solution and centrifuge it. Finally, redisperse it in an n-octane solution for storage.
[0057] In some embodiments, in step S52, the concentration of PbBr2 is 13.7 mg / ml.
[0058] In some embodiments, in step S52, the concentration of ZnBr2 is 51.15 mg / ml.
[0059] In some embodiments, the chemical formula of 3,3'-[1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl]bis(propan-1-ammonium) bromide is C 20 H 22 Br2N4O4, chemical structure formula is:
[0060] .
[0061] In some embodiments, in step S52, the amount of 3,3'-[1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl]bis(propane-1-ammonium) bromide added is in the range of 5-20 mg.
[0062] Example 1 (control group):
[0063] (1) Synthesis and purification of quantum dot materials:
[0064] Prepare two 100ml glass three-necked flasks, clean them with deionized water and ethanol, blow dry them, and put in a clean magnet. Put 0.137g PbBr2 and 0.511g ZnBr2 into the first three-necked flask and add 10ml octadecene as the first precursor solution. Add 0.18g Cs2CO3 and 1ml oleic acid into the second three-necked flask and add 10ml octadecene as the second precursor solution. Heat the above two bottles of solution to 60℃ and evacuate, and keep stirring under this condition for 30mins. Then fill the two flasks with nitrogen and evacuate immediately. After three cycles, heat them to 120℃ and keep stirring under vacuum for 30mins. Thereafter, adjust the heating temperature of the two flasks to 100℃ and fill the flasks with nitrogen. When the temperature of the first flask reaches 100℃, use a syringe to drop 2ml oleic acid and 3.5ml oleylamine into the first precursor solution and stir for 1 mins. After the solid in the solution is completely dissolved, the transparent solution in the bottle is vacuumed for 2 minutes, and then the solution is heated to 150°C under nitrogen. At this time, 1 ml of Cs-OA solution is extracted from the No. 2 precursor solution and quickly injected into the No. 1 flask. After reacting for 5 seconds, the No. 1 flask is placed in the prepared ice water to cool. The cooled perovskite quantum dot crude solution is transferred to a centrifuge tube and 40 ml of ethyl acetate is added, and centrifuged at 11000 rpm for 1 minute. Subsequently, the supernatant is discarded and the precipitate obtained after centrifugation is redispersed in 4 ml of n-octane solvent, and 8 ml of ethyl acetate is added to the above solution and centrifuged again at the same speed for 1 minute. The supernatant is discarded and the precipitate is dissolved in 1.5 ml of n-octane. After the precipitate is completely dispersed, centrifuge at a low speed of 5500 rpm for 5 minutes to remove large particles. Finally, the supernatant obtained by low-speed centrifugation is filtered through a 0.22 micron filter head and filled into a clean glass bottle and sealed for storage.
[0065] (2) Preparation of quantum dot light-emitting devices:
[0066] The glass substrate printed with ITO was ultrasonically cleaned with deionized water and anhydrous ethanol for 15 minutes, and treated with ultraviolet ozone for 15 minutes. The filtered PEDOT:PSS was then spin-coated on the ITO substrate (at a speed of 4000 rpm for 40 seconds) as a hole transport layer and annealed at 150 degrees Celsius for 15 minutes. Then, PVK was dissolved in chlorobenzene at a concentration of 4 mg / ml and spin-coated on PEDOT:PSS at a speed of 1000 rpm for 40 seconds as a hole injection layer, and annealed at 160 degrees Celsius for 30 minutes. Perovskite quantum dots were spin-coated on the PVK film at a speed of 4000 rpm as a light-emitting layer, and annealed at 60 degrees Celsius for 5 minutes. Finally, the spin-coated substrate was transferred to the evaporator, and TPBi, LiF and Al were evaporated in sequence as the electron transport layer and metal electrode, with thicknesses of 80 nm, 1 nm and 100 nm, respectively.
[0067] Embodiment 2:
[0068] (1) Synthesis and purification of quantum dot materials:
[0069] Prepare two glass three-necked flasks with a volume of 100 ml, wash with deionized water and ethanol, blow dry, and put in a clean magnet. Put 0.137g PbBr2, 0.511g ZnBr2 and 5mg TOPB2 into the first three-necked flask and add 10ml octadecene as the first precursor solution, add 0.18g Cs2CO3 and 1ml oleic acid into the second three-necked flask and add 10ml octadecene as the second precursor solution. The rest is the same as Example 1.
[0070] (2) Preparation of quantum dot light-emitting devices:
[0071] This part is exactly the same as Example 1.
[0072] Embodiment 3:
[0073] (1) Synthesis and purification of quantum dot materials:
[0074] Prepare two glass three-necked flasks with a volume of 100 ml, wash with deionized water and ethanol, blow dry, and put in a clean magnet. Put 0.137g PbBr2, 0.511g ZnBr2 and 10mg TOPB2 into the first three-necked flask and add 10ml octadecene as the first precursor solution, add 0.18g Cs2CO3 and 1ml oleic acid into the second three-necked flask and add 10ml octadecene as the second precursor solution. The rest is the same as Example 1.
[0075] (2) Preparation of quantum dot light-emitting diodes:
[0076] This part is the same as Example 1.
[0077] Embodiment 4:
[0078] (1) Synthesis and purification of quantum dot materials:
[0079] Prepare two glass three-necked flasks with a volume of 100 ml, wash with deionized water and ethanol, blow dry, and put in a clean magnet. Put 0.137g PbBr2, 0.511g ZnBr2 and 15mg TOPB2 into the first three-necked flask and add 10ml octadecene as the first precursor solution, add 0.18g Cs2CO3 and 1ml oleic acid into the second three-necked flask and add 10ml octadecene as the second precursor solution. The rest is the same as Example 1.
[0080] (2) Preparation of quantum dot light-emitting diodes:
[0081] This part is the same as Example 1.
[0082] Embodiment 5:
[0083] (1) Synthesis and purification of quantum dot materials:
[0084] Prepare two glass three-necked flasks with a volume of 100 ml, wash with deionized water and ethanol, blow dry, and put in a clean magnet. Put 0.137g PbBr2, 0.511g ZnBr2 and 20mg TOPB2 into the first three-necked flask and add 10ml octadecene as the first precursor solution, add 0.18g Cs2CO3 and 1ml oleic acid into the second three-necked flask and add 10ml octadecene as the second precursor solution. The rest is the same as Example 1.
[0085] (2) Preparation of quantum dot light-emitting diodes:
[0086] This part is the same as Example 1.
[0087] EL peak wavelength (nm) External quantum efficiency of LED devices Example 1 502 4.8% Example 2 483 7% Example 3 475 9.6% Example 4 470 12.% Example 5 466 11.2%
[0088] Table 1 EL performance of perovskite quantum dot LEDs
[0089] It can be seen from Table 1 and the accompanying drawings that as the amount of TOPB2 added increases (Examples 1-5), the electroluminescent wavelength of the device undergoes a significant blue shift, which indicates that the TOPB2 bidentate ligand effectively increases the band gap of the light-emitting layer material. This is because the size of the material is reduced under the encapsulation of the bidentate ligand, which in turn enhances the quantum confinement effect of the material and increases the band gap of the material, thereby causing a blue shift in the luminescent wavelength. In addition, as the TOPB2 content increases (Examples 1-4), the EQE of the LED device is significantly improved, which is because the TOPB2 ligand phase has a stronger binding ability with the surface of the perovskite quantum dots than the traditional oleic acid and oleylamine ligands, which effectively reduces the defects on the surface of the material, thereby significantly improving the luminous efficiency. It is worth noting that if the amount of TOPB2 added is too much (Example 5), the EQE will decline, which may be due to the introduction of too many organic ammonium ions, resulting in the precursor being in an overly strong alkaline environment, which in turn causes the surface of the quantum dots to be damaged by the alkaline environment.
[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A quantum dot light-emitting device, characterized in that: The invention comprises a substrate printed with an ITO anode, a PEDOT:PSS hole transport layer, a PVK hole transport layer, a perovskite quantum dot light-emitting layer, a TPBi electron transport layer, a LiF electron transport layer and an Al cathode which are sequentially connected from one side to the other side.
2. The method for preparing a quantum dot light-emitting device according to claim 1, characterized in that the steps include: S1. Place the substrate printed with ITO anode into a mixed solution of anhydrous ethanol and deionized water, and use an ultrasonic machine to ultrasonicate for 20 minutes, and then blow dry the liquid on its surface with nitrogen; S2, placing the dried substrate printed with ITO anode into UV cleaning agent and cleaning with UV ozone for 15 minutes; S3, spin-coat a PEDOT:PSS film on a clean substrate printed with an ITO anode using a coater and heat it on a hot plate for 15 minutes; S4, placing the product treated in step S2 into a glove box filled with nitrogen, spin-coating PVK, and heating it on a hot plate for 20 minutes; S5, after being cooled by the treatment of S3, spin coating the perovskite quantum dot light-emitting layer on the PVK film at a rotation speed of 4000 rpm, and heating at 60° C. for 5 minutes; S6: Place the product treated in S4 into the evaporation equipment and evacuate the air. When the air pressure is less than 5×10 -4 TPBi, LiF and AL thin films were evaporated at pa with thicknesses of 80nm, 1nm and 100nm, respectively.
3. The method for preparing a quantum dot light-emitting device according to claim 2, characterized in that: The synthesis and purification process of perovskite quantum dot light-emitting layer materials includes the following steps: S51, prepare two three-necked flasks, No. 1 and No. 2, each of which has a capacity of 100 ml, and place a stirring bar in each of the three-necked flasks; S52, PbBr2, ZnBr2 and 3,3'-[1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl]bis(propane-1-ammonium) bromide are placed in a No. 1 three-necked flask, and octadecene is added as a solvent; S53, adding Cs2CO3 and oleic acid into a No. 2 three-necked flask, and adding octadecene as a solvent; S54, heating the solutions in the No. 1 three-necked flask and the No. 2 three-necked flask to 120° C. and evacuating the solution, and maintaining this condition with stirring for one hour, then filling the two three-necked flasks with nitrogen and continuing to stir; S55, lowering the temperature of the two flasks to 100°C and adding oleic acid and oleylamine into the stirred three-necked flask No. 1, and evacuating the solution again after the solids in the solution are completely dissolved, and switching back to the nitrogen environment after 1 minute; S56, heating the No. 1 three-necked flask to 150° C., taking 1 ml of the Cs-OA solution from the No. 2 three-necked flask and quickly injecting it into the No. 1 three-necked flask, reacting for 5 seconds, and then cooling the No. 1 three-necked flask in an ice bath to obtain a crude perovskite quantum dot solution; S57. Add 20 ml of ethyl acetate to the cooled crude perovskite quantum dot solution and centrifuge it. Finally, redisperse it in an n-octane solution for storage.
4. The method for preparing a quantum dot light-emitting device according to claim 3, characterized in that: In step S52, the concentration of PbBr2 is 13.7 mg / ml.
5. The method for preparing a quantum dot light-emitting device according to claim 3, characterized in that: In step S52, the concentration of ZnBr2 is 51.15 mg / ml.
6. The method for synthesizing and purifying the quantum dot light-emitting layer material according to claim 3, characterized in that: The chemical formula of 3,3'-[1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl]bis(propane-1-ammonium) bromide is C 20 H 22 Br2N4O4, chemical structure formula is: 。 7. The method for synthesizing and purifying the quantum dot light-emitting layer material according to claim 3, characterized in that: In step S52, the amount of 3,3'-[1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl]bis(propane-1-ammonium) bromide added is in the range of 5-20 mg.
Citation Information
Patent Citations
Benzene-naphthalene diimide derivative, preparation method and its application
CN101550104A
Naphthalene diimide derivative as well as preparation method and application thereof
CN109134514A
Novel conjugated micromolecular inner salt containing sulfonate quaternary ammonium salt as well as preparation method and application thereof
CN112442034A
Preparation method of halogen-free ion migration blue-light inorganic perovskite quantum dots
CN113930242A
Perovskite quantum dot film, preparation method thereof and light-emitting diode
CN116600619A